2021
DOI: 10.1177/0192513x211022394
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dyadic Coping for the Individual and Relational Well-Being of Couples During the Transition to Parenthood

Abstract: Becoming parents represents a potentially stressful transition, which may negatively affect the individual and relational well-being of both partners. Limited literature has investigated the role of dyadic coping during the transition to parenthood. This work explored partners’ differences in dyadic coping, anxiety, depression, and couple adjustment during pregnancy and 3 months postpartum. Furthermore, through Actor–Partner Interdependence Model analyses, the relationship between common dyadic coping and well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
(90 reference statements)
1
4
0
Order By: Relevance
“…The findings of this study align with prior studies (Alizade, 2022;Falconier et al, 2023;Hiefner, 2021;Isanejad & Alizade, 2020;Kärner et al, 2021;Markman et al, 2022;Molgora et al, 2022;Omidian et al, 2019;Rauer et al, 2020;Ştefǎnuţ et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The findings of this study align with prior studies (Alizade, 2022;Falconier et al, 2023;Hiefner, 2021;Isanejad & Alizade, 2020;Kärner et al, 2021;Markman et al, 2022;Molgora et al, 2022;Omidian et al, 2019;Rauer et al, 2020;Ştefǎnuţ et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the Couples Coping Enhancement Program, through the skills it provides to couples, reduces their marital conflicts following childbirth. This program helps couples understand the new stressful and tense situation they face upon becoming parents, using criteria such as controllability, changeability, ambiguity, and certainty, enabling them to manage the conflict situation better through effective coping strategies and focusing on discussions about the conflict using clear, constructive, and non-coercive responses (Molgora et al, 2022). This ensures that instead of engaging in conflict, couples are on the right path and seeking solutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a randomized controlled trial of 348 pregnant couples, showed that a brief, two-session intervention aimed to enhance dyadic coping and communication skills, nested within a broader health behaviour intervention, buffered against declines in relationship satisfaction during the postpartum period (Coop Gordon et al, 2018). Finally, a longitudinal study found that women who gave birth and partners’ common dyadic coping in the third trimester of pregnancy predicted women’s higher scores on couple adjustment 3-months postpartum (Molgora et al, 2021). Taken together, dyadic coping has been positively linked to relationship satisfaction in community couples, and to marital satisfaction and couple adjustment for couples in the transition to parenthood.…”
Section: Links Between Dyadic Coping and Sexual Desire Sexual Satisfa...mentioning
confidence: 99%